2016
DOI: 10.1039/c6fo00328a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Schisandra chinensis extracts on depression by noradrenergic, dopaminergic, GABAergic and glutamatergic systems in the forced swim test in mice

Abstract: Schisandra chinensis (Turcz.) Baill., as a Chinese functional food, has been widely used in neurological disorders including insomnia and Alzheimer's disease. The treatment of classical neuropsychiatric disorder depression is to be developed from Schisandra chinensis. The antidepressant-like effects of the Schisandra chinensis extracts (SCE), and their probable involvement in the serotonergic, noradrenergic, dopaminergic, GABAergic and glutamatergic systems were investigated by the forced swim test (FST). Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…We know that the co-administration of antidepressant drugs may display a stronger effect or faster onset speed than single drug treatment. 22 In the present study, the results demonstrated that Sit-S and uoxetine, as well as Sit-S and reboxetine, displayed synergistic effects in combination. Effect of co-treatment of Sit-S with agomelatine, haloperidol and bicuculline on the 5-HT, DA and GABA levels in the brains of mice exposed to the TST.…”
Section: Resultssupporting
confidence: 55%
“…We know that the co-administration of antidepressant drugs may display a stronger effect or faster onset speed than single drug treatment. 22 In the present study, the results demonstrated that Sit-S and uoxetine, as well as Sit-S and reboxetine, displayed synergistic effects in combination. Effect of co-treatment of Sit-S with agomelatine, haloperidol and bicuculline on the 5-HT, DA and GABA levels in the brains of mice exposed to the TST.…”
Section: Resultssupporting
confidence: 55%
“…The decrease of total traveled distance, central distance ratio, and central time in OFT indicate a lower desire to explore, which may mimic psychomotor retardation [24]. Additionally, the low levels of rearing in OFT, and the increased immobility time in FST are often used as indices of a despair state [25, 26]. The rats exhibited improvement of depressive-like behaviors in OFT and in FST after HJDT or paroxetine treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Sour and salty components are believed to have good effects on the liver and testicles, bitter and stringent ones are believed to have good effects on the heart and lungs, and sweet component is believed to have good effects on the stomach [22]. In addition, numerous clinical trials have reported the efficacy of SF in conditions such as cough, dyspnea, dysentery, insomnia, amnesia, tumor, CNS, and cardiotonic disorder [18, 50, 51]. In Korea, SF is used in various herbal prescriptions for the treatment of menopausal symptoms, including Pheongbojinsimdan, Gamiondamtang, and Insugsan [18].…”
Section: Discussionmentioning
confidence: 99%